Improving Boer goat sperm cryopreservation efficiency using sucrose and ascorbic acid as cryoprotectants - Tran Thi Thanh Khuong; Nguyen Lam Khanh Duy; Nguyen Nhat Tan; Ho Hoang Anh; Lam Phuoc Thanh (Agriculture and Natural Resources, 2026)
Importance of the work: Cryopreservation of goat sperm is known to cause damage that reduces the sperm's motility, viability, acrosome integrity and antioxidant rate. Objectives: To optimize Boer goat sperm cryopreservation by adding sucrose and ascorbic acid as cryoprotectants in the medium. Materials and Methods: Experiment 1 tested four concentrations of sucrose (0 M, 0.025 M, 0.05 M, 0.1 M). Experiment 2 tested four concentrations of ascorbic acid (0 µM, 40 µM, 60 µM, 80 µM) combined with the optimal sucrose concentration determined from Experiment 1. After 72 hr of storage in liquid nitrogen, sperm quality parameters were assessed. Results: Based on the results from Experiment 1, 0.05 M sucrose was the optimal concentration for goat sperm preservation with mean ± SD values for overall motility, progressive motility, viability, membrane integrity and acrosome integrity of 75.50 ± 0.68, 59.17 ± 0.64, 79.71 ± 0.42, 63.11 ± 0.55and 83.09 ± 0.75, respectively (p < 0.05). Based on the results from Experiment 2, the combination of 0.05 M sucrose and 60 µM ascorbic acid significantly (p < 0.05) improved sperm quality, with values for overall motility of 81.88 ± 1.73%, progressive motility of 69.13 ± 0.71%, viability of 81.96 ± 1.44%, membrane integrity of 68.33 ± 1.60%, antioxidant rate of 49.60 ± 1.53% and acrosome integrity of 93.13 ± 1.19%. Main finding: The cryopreservation medium supplemented with 0.05 M sucrose and 60 µM ascorbic acid protected Boer goat sperm during preservation. The findings highlighted the synergistic effects of sucrose and ascorbic acid, suggesting their potential to greatly enhance goat sperm cryopreservation outcomes